Contenido estomacal de Spondylus leucacanthus (Bivalvia: Spondylidae) y su relación con la temporada de reproducción y la abundancia de fitoplancton en Isla Danzante, Golfo de California - Muñetón-Gómez, María del Socorro (2001)
During 1994 we collected specimens of Spondylus leucacanthus near Isla Danzante, Gulf of California. We measured seawater temperature, and sampled stomach contents and phytoplankton. The reproductive season was assessed through the gonadic index. There is a cool season from December to May and a warm season from June to November. The stomach content was composed of detritus (60%), phytoplankton (30%), and unidentified materials (10%). The highest abundance of phytoplankton cells in the bottom water and the stomach content were in March, April, and May, during the seasonal change of temperature. The gonadic index showed a single peak, confirming that the population has an annual pattern of reproduction. The start of gametogenic phase and maturity in the population coincide with the abundance of phytoplankton